Pembrolizumab and maraviroc in refractory mismatch repair proficient/microsatellite-stable metastatic colorectal cancer – The PICCASSO phase I trial. (May 2022) - Haag, Georg Martin; Springfeld, Christoph; Grün, Barbara; Apostolidis, Leonidas; Zschäbitz, Stefanie; Dietrich, Mareike; Berger, Anne-Katrin; Weber, Tim Frederik; Zoernig, Inka; Schaaf, Marina; Waberer, Lisa; Müller, Daniel Wilhelm; et al.
Abstract: Background: PD-1/PD-L1 inhibitors do not show activity in mismatch repair proficient (MMRp) colorectal cancer. Inhibition of C–C motif chemokine receptor 5 (CCR5) leads to an antitumoral activation of macrophages, affecting immune cell infiltrates. PICCASSO is a phase I trial exploring safety and efficacy of pembrolizumab and maraviroc in refractory MMRp CRC. Methods: Twenty patients received pembrolizumab and maraviroc (core period, eight cycles), followed by pembrolizumab monotherapy. Primary endpoint was the feasibility rate (patients without treatment-related grade ≥3 immune-related adverse events, treatment-related grade ≥4 adverse events, or any toxicity-related premature withdrawal of treatment). Secondary endpoints included safety/toxicity, overall response rate (ORR), progression-free survival (PFS), and overall survival (OS). Optional biopsies of liver metastases were performed for analyses of the micromilieu. Results: The feasibility rate was 94.7% [90% CI 77.4–99.7%], with one grade 4 hyperglycemia and no additional ≥ grade 3 treatment-related toxicities. ORR according to RECIST was 5.3%. Median PFS according to RECIST was 2.10 months [95%CI 1.68–2.30], median OS 9.83 months [95% CI, 5.59–20.02]. Disease control rate of poststudy salvage treatment was >70%. Translational analyses showed an increase of antitumoral chemokines during treatment; eotaxin, a chemokine involved in chemotaxis, was identified as a biomarker linked to OS. Conclusions: Therapy with pembrolizumab and maraviroc was feasible and showed a beneficial toxicity pattern. Clinical activity in MMRp CRC patients was limited with prolonged disease stabilizations observed in single patients. Efficacy of poststudy salvage treatment and OS was higher than expected in this heavily pretreated population. This trial is registered at clinicaltrials.gov: NCT03274804. Highlights: Combined CCR5 and PD-1 blockade shows a beneficial toxicity pattern in MMRp CRC. Though clinical activity was limited, overall survival was longer than expected. A high efficacy of poststudy salvage treatment was observed. Translational analyses showed an alteration of the micromilieu.